2017
DOI: 10.1007/978-3-319-61194-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Managing Environmental Risk in Presence of Climate Change: The Role of Adaptation in the Nile Basin of Ethiopia

Abstract: This study investigates the impact of climate change adaptation on farm households' downside risk exposure in the Nile Basin of Ethiopia. The analysis relies on a moment-based specification of the stochastic production function. We use an empirical strategy that accounts for the heterogeneity in the decision on whether to adapt or not, and for unobservable characteristics of farmers and their farm. We find that past adaptation to climate change (i) reduces current downside risk exposure, and subsequently the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…Technology adoption could, however, provide additional benefits such as risk management (e.g. Di Falco and Veronesi, 2014;Kassie et al, 2015c) and environmental benefits (e.g. Teklewold et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Technology adoption could, however, provide additional benefits such as risk management (e.g. Di Falco and Veronesi, 2014;Kassie et al, 2015c) and environmental benefits (e.g. Teklewold et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…included to control for unobserved heterogeneity following Mundlak (1978) and Wooldridge (2002). Studies that have used this approach using cross-sectional multiple plot observations include Kassie et al (2008) andVeronesi (2014). D, T, S, M, V, and F denote crop diversification, minimum tillage, soil and water conservation measure, manure use, improved maize varieties, and inorganic fertilizer use, respectively.…”
Section: Conceptual Framework Model Specification and Estimation Strmentioning
confidence: 99%
“…Gray and Muller (2012) reported that drought is a significant negative shock that can undermine the livelihood of the people, who depend on agriculture. Over the past three decades, Ethiopia has been overwhelmed by climate variability and associated droughts that resulted profound effects on the country's food production and employment (Benson and Clay, 1998;Bewket and Conway, 2007;Araya and Stroosnijder, 2011;Conway and Schipper, 2011;Falco, 2012). The frequent droughts in turn affected the income of the rural poor who fully depend on agriculture as droughts can result in reductions in crop outputs by as much as 90 per cent from a normal rainfall period (WFP, 2009).…”
Section: Introductionmentioning
confidence: 99%